A paradox of the social production of urban space: environmental sustainability and vulnerable territories in Londrina/PR/Brazil - Antonello, Ideni Terezinha (National Journal of City Management, 2023)
The social production of urban space is marked by the segregationist pattern. This encourages denial of decent housing for a portion of the Brazilian population, which has to seek vulnerable territories (favelas) as a survival strategy. The aim of this article is to present the reality scenario where these vulnerable territories (favelas) are present in the urban space of Londrina/PR, which unfolds in the concern to enter into the paradox between the formal construction environment and these territories, as most of them are located in areas of permanent preservation (APP's), which by precept of the Laws: Forest Code (2012) Environmental Code of Londrina (2012), should be preserved. A qualitative approach was the used methodology in the research, with the theoretical-methodological framework based on Lefebvre (2006) and primary and secondary sources were used to obtain the data. Environmental laws clash with the information obtained in the survey: the existence of 69 vulnerable territories, with 3,160 families (10,867 people, 2017) rising to 3,815 families (12,240 people) in 2020 (LONDRINA, 2021). This reality results in the lack of convergence between the territorial planning policy (PDM) and policies such as: environmental, housing, environmental sanitation (other sectoral policies) that should be integrated in favor of the development of inclusive and socially and environmentally sustainable cities, which could contribute to overcoming the paradox of the social production of space